2022
DOI: 10.1002/jmri.28303
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2D and 4D Flow MRI in Neonates Without General Anesthesia

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…However, despite equal positions of the measurement planes at the atrium and aortic valve, differences in velocity measurements were still observed. It has been shown that 4D PC-MRI data may underestimate peak velocities [29], [30], which may account for the observed differences. Additionally, the spatial standard deviation in 4D PC-MRI measurements is larger than in the 2D PC-MRI data, thus a higher variation in velocity in the 4D PC-MRI data was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite equal positions of the measurement planes at the atrium and aortic valve, differences in velocity measurements were still observed. It has been shown that 4D PC-MRI data may underestimate peak velocities [29], [30], which may account for the observed differences. Additionally, the spatial standard deviation in 4D PC-MRI measurements is larger than in the 2D PC-MRI data, thus a higher variation in velocity in the 4D PC-MRI data was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…This would allow PEPT to measure both blood velocity and functional pressure drop over an occlusion, in contrast to conventional PET, which can only measure perfusion over tissue volumes [ 79 ]. Cardiac 4D phase-contrast CMR can measure flow at a resolution of 1.5x1.5x1.5 to 3×3×3 mm 3 [ 4 , 5 ] with a dependency on the users’ experience [ 80 ], which would limit their ability to measure flow across an occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Invasively, one can measure the pressure difference along a lesion during coronary angiography [ 1 ] to calculate the Fractional Flow Reserve (FFR), which links to the severity of the disease. To avoid invasive procedures, techniques such as coronary computed tomography (CT) [ 2 , 3 ], 4D MRI [ 4 , 5 ], and cardiac Positron Emission Tomography (PET) [ 6 ] have been used. However, all the current techniques are associated with various uncertainties and challenges.…”
Section: Introductionmentioning
confidence: 99%
“…SNR and VNR improve with T1 shortening achieved by administering gadolinium-based contrast [ 48 , 49 ] or superparamagnetic iron oxide agent (ferumoxytol) [ 50 ]. Therefore, contrast administration to enhance image quality can be useful (but is not essential), especially in challenging cases such as neonates and dissections to enhance image quality, but good image quality can be achieved without contrast administration especially when scanning at 3T [ 51 , 52 ]. In adults, if contrast is given for other reasons, it is useful to perform the 4D Flow CMR acquisition after gadolinium-based contrast administration.…”
Section: Advised Acquisition Parameters For Clinical Usementioning
confidence: 99%